Novel scheme for non-invasive gut bioinformation acquisition with a magnetically controlled sampling capsule endoscope. Issue 12 (15th January 2021) - Ding, Zhen; Wang, Weijun; Zhang, Kun; Ming, Fanhua; Yangdai, Tianyi; Xu, Tao; Shi, Huiying; Bao, Yuhui; Yao, Hailing; Peng, Hangyu; Han, Chaoqun; Jiang, Weiwei; et al.
Abstract : Objective: Intestinal flora and metabolites are associated with multiple systemic diseases. Current approaches for acquiring information regarding microbiota/metabolites have limitations. We aimed to develop a precise magnetically controlled sampling capsule endoscope (MSCE) for the convenient, non-invasive and accurate acquisition of digestive bioinformation for disease diagnosis and evaluation. Design: The MSCE and surgery were both used for sampling both jejunal and ileal GI content in the control and antibiotic-induced diarrhoea groups. The GI content was then used for microbiome profiling and metabolomics profiling. Results: Compared with surgery, our data showed that the MSCE precisely acquired data regarding the intestinal flora and metabolites, which was effectively differentiated in different intestinal regions and disease models. Using MSCE, we detected a dramatic decrease in the abundance of Bacteroidetes, Patescibacteria and Actinobacteria and hippuric acid levels, as well as an increase in the abundance of Escherichia–Shigella and the 2-pyrrolidinone levels were detected in the antibiotic-induced diarrhoea model by MSCE. MSCE-mediated sampling revealed specific gut microbiota/metabolites including Enterococcus, Lachnospiraceae, acetyl-L-carnitine and succinic acid, which are related to metabolic diseases, cancers and nervous system disorders. Additionally, the MSCE exhibited good sealing characteristics with no contamination after sampling. Conclusions: We present a newly developed MSCE that can non-invasively and accurately acquire intestinal bioinformation via direct visualization under magnetic control, which may further aid in disease prevention, diagnosis, prognosis and treatment.